Low-dose aspirin use and recurrent gout attacks. Issue 2 (23rd January 2013) - Zhang, Yuqing; Neogi, Tuhina; Chen, Clara; Chaisson, Christine; Hunter, David J; Choi, Hyon
Abstract : Objective: To examine the association between cardioprotective use of low-dose aspirin and the risk of recurrent gout attacks among gout patients. Methods: We conducted an online case-crossover study of individuals with gout over 1 year. The following information was obtained during gout attacks: the onset dates, symptoms and signs, medications, and exposure to potential risk factors, including daily aspirin use and dosage, during the 2-day hazard period prior to the gout attacks. The same exposure information was also obtained over 2-day control periods. Results: Of the 724 participants analysed, 40.5% took aspirin ≤325 mg/day during either a hazard or a control period. Compared with no aspirin use, the adjusted OR of gout attacks increased by 81% (OR=1.81, 95% CI 1.30 to 2.51) for ≤325 mg/day of aspirin use on two consecutive days. The corresponding ORs were stronger with lower doses (eg, OR=1.91 for ≤100 mg, 95% CI 1.32 to 2.85). These associations persisted across subgroups by sex, age, body mass index categories and renal insufficiency status. Concomitant use of allopurinol nullified the detrimental effect of aspirin. Conclusions: Our findings suggest that the use of low-dose aspirin on two consecutive days is associated with an increased risk of recurrent gout attacks. Recommended serum urate monitoring with concomitant use and dose adjustment of a urate-lowering therapy among patients with gout may be especially important to help avoid the risk of gout attacks associated with low-dose aspirin.